Fiscal policy, the Sraffian supermultiplier and functional finance - Peter Skott; Júlio Fernando Costa Santos; José Luís Da Costa Oreiro (University of Massachusetts, Department of Economics, 2020)
Sraffian supermultiplier models (SSM) try to identify autonomous components of demand. The most plausible candidate is government consumption. Descriptively, however, government consumption does not grow at a constant rate, and prescriptively there is no justification for keeping constant the growth rate of government consumption, irrespective of economic performance. An active fiscal policy guided by principles of functional finance can produce more powerful stabilization, avoid overheating and excessive utilization rates, and secure faster adjustments of the growth rate towards its target level.
Keywords: 330; Öffentlicher Konsum; Finanzpolitik; Wachstumstheorie; Neo-Ricardianische Schule